Job satisfaction among radiology assistants: a multicentre cross-sectional study in Italy - Gualano, Maria Rosaria; Gili, Renata; Bert, Fabrizio; Scaioli, Giacomo; Cerutti, Stefano; Gatti, Giovanni; Siliquini, Roberta (La Medicina del Lavoro, 2016)
Objectives: Job satisfaction among physicians is an important occupational health issue since it is related to different factors such as work motivation or career decisions. The aim of this study was to investigate job satisfaction among radiology assistants for the first time in Italy. Methods: In 2012, a cross-sectional survey was conducted among a convenience sample of radiology assistants drawn from all Italian regions who submitted an electronic or paper-based self-administered questionnaire. The data collected were analysed using logistic regressions in order to assess the role of socio-demographic variables. Results: Overall, 574 radiology assistants were interviewed. More than half of the subjects were males and were younger than 40 years old. Around 76% of the sample was not satisfied as regards salary. Moreover, the majority of the participants (66.1%) was not satisfied with the professional refresher courses. Compared with males, females were more satisfied in terms of professional enrichment (OR=1.79, 95% CI: 1.23-2.62) but less satisfied with their relationships with superiors (OR=0.57, 95% CI: 0.38-0.85). Conclusions: Since radiology assistants and, in general, healthcare workers assist medical doctors, thus playing a significant role in safeguarding patients’ health , it would be desirable to give due importance to the issue of job satisfaction, from all points of view.